A Fibonacci series

Calculus Level 3

Let F n F_n be the n n th Fibonacci number, where F 1 = 1 F_1=1 , F 2 = 1 F_2=1 and F n + 1 = F n + F n 1 F_{n+1}=F_n+F_{n-1} , for n 2 n \geq 2 . Evaluate the sum n = 2 F n F n + 1 F n 1 . \sum_{n=2}^\infty \frac{F_n}{F_{n+1} F_{n-1}}.


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Santi Spadaro
Aug 10, 2018

Using the definition of the Fibonacci sequence we see that: F n = F n + 1 F n 1 F_n=F_{n+1}-F_{n-1} . We can use this information to turn the series of the problem into a telescoping series.

n = 2 F n F n + 1 F n 1 = n = 2 F n + 1 F n 1 F n + 1 F n 1 = n = 2 ( 1 F n 1 1 F n + 1 ) = lim N n = 2 N ( 1 F n 1 1 F n + 1 ) = \sum_{n=2}^\infty \frac{F_n}{F_{n+1} \cdot F_{n-1}}=\sum_{n=2}^\infty \frac{F_{n+1}-F_{n-1}}{F_{n+1} \cdot F_{n-1}}=\sum_{n=2}^\infty \left (\frac{1}{F_{n-1}} - \frac{1}{F_{n+1}}\right )=\lim_{N \to \infty} \sum_{n=2}^N \left (\frac{1}{F_{n-1}}-\frac{1}{F_{n+1}} \right )=

= lim N ( 1 F 1 1 F 3 + 1 F 2 1 F 4 + 1 F 3 1 F 5 + . . . + 1 F N 2 1 F N + 1 F N 1 1 F N + 1 ) = lim N ( 1 F 1 + 1 F 2 1 F N 1 F N + 1 ) = 1 F 1 + 1 F 2 0 0 = 1 + 1 = 2 =\lim_{N \to \infty} \left (\frac{1}{F_1}-\frac{1}{F_3}+\frac{1}{F_2}-\frac{1}{F_4}+\frac{1}{F_3}-\frac{1}{F_5}+...+\frac{1}{F_{N-2}}-\frac{1}{F_N}+\frac{1}{F_{N-1}}-\frac{1}{F_{N+1}}\right )=\lim_{N \to \infty} \left (\frac{1}{F_1}+\frac{1}{F_2}-\frac{1}{F_N}-\frac{1}{F_{N+1}}\right )=\frac{1}{F_1}+\frac{1}{F_2}-0-0=1+1=2

Chew-Seong Cheong
Aug 12, 2018

Similar solution with @Santi Spadaro 's

S = n = 2 F n F n + 1 F n 1 Note that F k = F k 1 + F k 2 = n = 2 F n ( F n + F n 1 ) F n 1 = n = 2 ( 1 F n 1 1 F n + F n 1 ) = n = 2 ( 1 F n 1 1 F n + 1 ) = n = 1 ( 1 F n 1 F n + 2 ) = 1 F 1 1 F 3 + 1 F 2 1 F 4 + 1 F 3 1 F 5 + 1 F 4 1 F 6 + = 1 F 1 1 F 3 + 1 F 2 1 F 4 + 1 F 3 1 F 5 + 1 F 4 1 F 6 + = 1 F 1 + 1 F 2 = 2 \begin{aligned} S & = \sum_{n=2}^\infty \frac {F_n}{{\color{#3D99F6}F_{n+1}}F_{n-1}} & \small \color{#3D99F6} \text{Note that }F_k = F_{k-1} + F_{k-2} \\ & = \sum_{n=2}^\infty \frac {F_n}{{\color{#3D99F6}\left(F_n+F_{n-1}\right)}F_{n-1}} \\ & = \sum_{n=2}^\infty \left(\frac 1{F_{n-1}} - \frac 1{F_n+F_{n-1}} \right) \\ & = \sum_{\color{#3D99F6}n=2}^\infty \left(\frac 1{F_{\color{#3D99F6}n-1}} - \frac 1{F_{\color{#3D99F6}n+1}} \right) \\ & = \sum_{\color{#D61F06}n=1}^\infty \left(\frac 1{F_{\color{#D61F06}n}} - \frac 1{F_{\color{#D61F06}n+2}} \right) \\ & = \frac 1{F_1} - \frac 1{F_3} + \frac 1{F_2} - \frac 1{F_4} + \frac 1{F_3} - \frac 1{F_5} + \frac 1{F_4} - \frac 1{F_6} + \cdots \\ & = \frac 1{F_1} - {\color{#3D99F6}\cancel{\frac 1{F_3}}} + \frac 1{F_2} - {\color{#D61F06}\cancel{\frac 1{F_4}}} + {\color{#3D99F6}\cancel{\frac 1{F_3}}} - \cancel{\frac 1{F_5}} + {\color{#D61F06}\cancel{\frac 1{F_4}}} - \cancel{\frac 1{F_6}} + \cdots \\ & = \frac 1{F_1} + \frac 1{F_2} = \boxed 2 \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...